Modern Malay Rhythm Music Trend as Popular Culture in Indonesia, 1950-1960s: A Sociological Analysi - Alkatiri, Zeffry; Kamal, Mathar Moehammad (ASPENSI in Bandung, Indonesia, 2013)
ABSTRACT: This article discusses the phenomenon of rhythmic music that was once a popular Malay in Indonesia around Â 1950s to 1960s. This article will look at from the sociological context of community and content of the lyrics contained in the modern Malay music. The goal is to find out how changes in the Malay music, why can be liked, what kinds of messages contained in the lyric, as well as any supporting characters. Other research uses cultural studies approaches and discourse analysis. Data taken from the document research related to Malay songs and various writings. One of the creations which are considered radical innovations is changing the Malay rhythm to âdangdutâ rhythm. Hence, the appearance of several prominent modern Malay music-blooded Arab is very important. This shows that they have also directly contributed something meaningful to the people of Indonesia for the development of music in particular and Indonesia in general. Meanwhile, the results of this study can also be used to see the condition of Indonesian society that is undergoing a transition process of development and to review a popular culture phenomenon that has ever happened around the year 1950s to 1960s in Indonesia.KEY WORDS: Trend music, rhythm Malay, popular culture, âdangdutâ music, Indonesian-Arabs, and Indonesian society.Â Â About the Authors: Dr. Zeffry Alkatiri is a Senior Lecturer at the Department of History, Faculty of Humanities UI (University of Indonesia), UI Campus, Depok, West Java, Indonesia; and Mathar Moehammad Kamal is a Freelance Journalist dan Mass Media Resercher lived in Jakarta. They can be contacted via e-mail at: zeffry_al@yahoo.com and matharmoehammad@yahoo.comHow to cite this article? Alkatiri, Zeffry & Mathar Moehammad Kamal. (2013). âModern Malay Rhythm Music Trend as Popular Culture in Indonesia, 1950-1960s: A Sociological Analysiâ in TAWARIKH: International Journal for Historical Studies, Vol.4(2) April, pp.223-244. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 28, 2013); Revised (March 30, 2013); and Published (April 28, 2013).